Persepsi Masyarakat Kota Padangsidimpuan Tentang Program Ma’had Al-Jami’ah Iain Padangsidimpuan - Agustina Damanik (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
This study a problem ofpower in Islamic politics. The main problem in this paper is how power. Ulama and Umara in the structure of Islamic politics, through content analysis and conceptual approach it is gained an understanding that power comes from God and no one has absolute power. But that power is delegated to humans as representatives og God on earth who are given orders to establish a just government and realize shared prosperity. With this concept of power there is no longer a contradiction between the power of good and the human need for government. Ulama adn Umara in he structure are those who are required by teh Quran as ulu al amr or those who govern and must be obeyed because they consist of people who are elected and fulfill complementary requirements such as trustworthiness, courage, strength, common sense, and knowledge of knowledge, it is hoped that they will be able to become role models for all levels of society. They act as interpreters of rules that are not yet clear in the Quran and at the same time as supervisors af the contitutionality of goverment and administrator rules in order to convince the people that these rules do not violate the Shari’a. while the Umara or the goverment applies sharia laws.